RANCANGAN PEMBUATAN KONSEP MAPS VISUAL FLIGHT RULES (VFR) ROUTE WILAYAH UJUNG PANDANG FLIGHT INFORMATION CENTRE (FIC) BALIKPAPAN SECTOR BAGIAN SELATAN DALAM RANGKA PENINGKATAN KINERJA UNIT ATS-RO DI PERUM LPPNPI CABANG BALIKPAPAN - Fidela Nur Avisa; Meita Maharani Sukma; Siti Nurfadhilah (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The VFR route is made to facilitate the provision of services, both in terms of providing information on security and flight safety. Based on data in the field, VFR flights at Perum LPPNPI Balikpapan Branch do not yet have a definite visual flight route. This makes it a little difficult for ACO personnel to ensure the exact position of the aircraft, even though the provision of a flight path is an important aspect for aircraft to get maximum service. The research method used is a qualitative descriptive research design that uses 2 variables; Design of Maps VFR route (Variable X) and Work Improvement of ATS-RO Unit (Variable Y). Data collection techniques using; observation, literature study, and interviews. Interviews were conducted with 6 ACO personnel and 1 PANS-OPS Expert at Perum LPPNPI Balikpapan Branch. The results of this study indicate the need for procurement of maps of the southern VFR route in order to improve the performance of the ATS-RO unit at Perum LPPNPI Balikpapan Branch. So from the results of the study it can be concluded that the procurement of maps for the southern VFR route needs to be realized immediately in order to support the provision of maximum flight navigation services. Especially for visual flights operating in the Ujung Pandang area of ​​the FIC Balikpapan sector.